Changes in Air CO(2) Concentration Differentially Alter Transcript Levels of NtAQP1 and NtPIP2;1 Aquaporin Genes in Tobacco Leaves - Secchi, Francesca (Int J Mol Sci, 2016)
The aquaporin specific control on water versus carbon pathways in leaves is pivotal in controlling gas exchange and leaf hydraulics. We investigated whether Nicotiana tabacum aquaporin 1 (NtAQP1) and Nicotiana tabacum plasma membrane intrinsic protein 2;1 (NtPIP2;1) gene expression varies in tobacco leaves subjected to treatments with different CO(2) concentrations (ranging from 0 to 800 ppm), inducing changes in photosynthesis, stomatal regulation and water evaporation from the leaf. Changes in air CO(2) concentration ([CO(2)]) affected net photosynthesis (Pn) and leaf substomatal [CO(2)] (Ci). Pn was slightly negative at 0 ppm air CO(2); it was one-third that of ambient controls at 200 ppm, and not different from controls at 800 ppm. Leaves fed with 800 ppm [CO(2)] showed one-third reduced stomatal conductance (g(s)) and transpiration (E), and their g(s) was in turn slightly lower than in 200 ppm– and in 0 ppm–treated leaves. The 800 ppm air [CO(2)] strongly impaired both NtAQP1 and NtPIP2;1 gene expression, whereas 0 ppm air [CO(2)], a concentration below any in vivo possible conditions and specifically chosen to maximize the gene expression alteration, increased only the NtAQP1 transcript level. We propose that NtAQP1 expression, an aquaporin devoted to CO(2) transport, positively responds to CO(2) scarcity in the air in the whole range 0–800 ppm. On the contrary, expression of NtPIP2;1, an aquaporin not devoted to CO(2) transport, is related to water balance in the leaf, and changes in parallel with g(s). These observations fit in a model where upregulation of leaf aquaporins is activated at low Ci, while downregulation occurs when high Ci saturates photosynthesis and causes stomatal closure.